Peningkatan Kinerja Ditinjau dari Kepemimpinan Transformasional, Motivasi Kerja dan Kedisiplinan melalui Kualitas Sumber Daya Manusia pada Sekretariat Jenderal Dewan Ketahanan Nasional - Ardiansyah, Reno; Mukrodi, Mukrodi (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This research aims to 1) To determine and analyze the influence of transformational leadership on the quality of human resources. 2) To determine and analyze the influence of work motivation on the quality of human resources. 3) To determine and analyze the influence of discipline on the quality of human resources. 4) To determine and analyze the influence of transformational leadership on employee performance. 5) To determine and analyze the influence of work motivation on employee performance. 6) To determine and analyze the influence of discipline on employee performance. 7) To determine and analyze the influence of the quality of human resources on the performance of Secretariat General Wantannas employees. The research method used in this research is a descriptive-quantitative statistical method using SmartPLS (Partial Least Square) software ver 3.2.8 with the PLS Analysis model. The population in this study was 140 people. In this research, the sampling technique used was simple random sampling. Thus, the number of saturated samples used was 100 respondents. The results of this research show that: 1) There is a positive and significant influence of Transformational Leadership on the Quality of Human Resources. 2) There is a positive and significant influence of work motivation on the quality of human resources. 3) There is a significant and significant influence of discipline on the quality of human resources. 4) There is a significant and significant influence of Transformational Leadership on Performance. 5) There is a positive and significant influence of work motivation on performance. 6) There is a positive and significant influence of discipline on performance. 7) There is a significant and significant influence on the quality of human resources on performance.